(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This article focuses on the concept of "spiritual renewal" and its essence. The spiritual life of the community focuses on spiritual activities, and spiritual relationships are widely covered in the article. The article also talks about spiritual values, the concept of spiritual renewal and its meaning.